2006
DOI: 10.1590/s0034-72992006000300012
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre tontura e disfunções do metabolismo da glicose

Abstract: Introducti on: Impaired glucose metabolism is characterized by conditions of hypo and hyperglycemia. Aim: The objective of the present study was to asses whether or not there is a relationship between impaired glucose metabolism and dizziness. In the clinical laboratory settings, patients were examined using vectoelectronystagmography in association with glycemic levels. Methods: 33 patients were divided in 3 groups: diabetics; patients with dizziness and a control group. Results:65% of the patients with dizzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
2
1
2
Order By: Relevance
“…On the other hand, there was no significant association between spinning vertigo and metabolic diseases such as diabetes mellitus in the studied population, going against findings in the literature (Fonseca & Davidsohn, 2006;Bittar, et al, 2003), despite the prevalence in the sample (16.7%) surpassing the prevalence of the Brazilian population aged 18 or over (6.2%) (IBGE, 2013). The results found may be related to the sample size, mainly due to the prevalence of Menière's disease in the population, etiology closely related to changes in glucose metabolism (D´avila & Lavinsky, 2005).…”
Section: Causes Of Dizzinesscontrasting
confidence: 74%
“…On the other hand, there was no significant association between spinning vertigo and metabolic diseases such as diabetes mellitus in the studied population, going against findings in the literature (Fonseca & Davidsohn, 2006;Bittar, et al, 2003), despite the prevalence in the sample (16.7%) surpassing the prevalence of the Brazilian population aged 18 or over (6.2%) (IBGE, 2013). The results found may be related to the sample size, mainly due to the prevalence of Menière's disease in the population, etiology closely related to changes in glucose metabolism (D´avila & Lavinsky, 2005).…”
Section: Causes Of Dizzinesscontrasting
confidence: 74%
“…In one of them (22), 65% of patients with dizziness had glucose alterations, which also is above population media. On the other hand, another authors (12) found fasting glucose levels changes in 7,6% of tinnitus patients.…”
Section: Discussionmentioning
confidence: 90%
“…Hormonal changes in women between the fourth and fifth decades of life mark the onset of climateric period, whose manifestations may include water retention and metabolic and anxiety disorders. 4 , 21 , 22 , 23 In this age group, GMD acts as a migraine trigger and can also be responsible for triggering postural disorders. 21 , 24 …”
Section: Discussionmentioning
confidence: 99%